2020
DOI: 10.1186/s13036-020-0231-y
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized chitosan stabilizes the bioactivity of BMP-2 and potentiates the osteogenic efficacy of demineralized bone matrix

Abstract: Background: Demineralized bone matrix (DBM), an allograft bone processed to better expose osteoinductive factors such as bone morphogenetic proteins (BMPs), is increasingly used for clinical bone repair. However, more extensive use of DBM is limited by its unpredictable osteoinductivity and low bone formation capacity. Commercial DBM products often employ polymeric carriers to enhance handling properties but such carriers generally do not possess bioactive functions. Heparin is a highly sulfated polysaccharide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…A recent study demonstrated that the use of DBM in combination with polymeric carriers could withhold, stabilize, and protect BMPs, resulting in the enhanced osteoinductivity. 29 In this study, a new hydrogel−siRNA conjugate is developed to enhance osteogenesis by guiding gene silencing and upregulating BMP signaling. The strategy to design a bioactive hydrogel was implemented by a two-step functionalization of methacrylate and sulfonate moieties.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that the use of DBM in combination with polymeric carriers could withhold, stabilize, and protect BMPs, resulting in the enhanced osteoinductivity. 29 In this study, a new hydrogel−siRNA conjugate is developed to enhance osteogenesis by guiding gene silencing and upregulating BMP signaling. The strategy to design a bioactive hydrogel was implemented by a two-step functionalization of methacrylate and sulfonate moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Heparinized chitosan has a protective effect on BMP bioactivity and can resist the physiological stressors related to fracture healing. It enhanced osteogenesis by inhibiting Noggin activity and attracted BMSCs ( Kim et al, 2020 ). Moreover, it exhibited synergetic effects between BMP-2 and VEGF, which effectively augmented bone formation stimulating osteogenesis and angiogenesis ( Zhang S et al, 2019 ).…”
Section: Application Of Heparin For Orthopedic Biomaterials Designmentioning
confidence: 99%
“…Heparin, chondroitin sulfate, and hyaluronic acid are GAGs that bind GFs and have been used for sustained release to improve tissue regeneration. Heparin is a highly sulfated, negatively charged polysaccharide that forms a stable complex with GFs through specific binding domains and electrostatic interactions and has been shown to enhance GF activity. , Various substrates have been functionalized with heparin to sequester GFs for bone, , cartilage, , and osteochondral repair. BMP-2 loaded heparin microparticles (HMPs) incorporated within alginate gels increased BMP-2 retention and resulted in robust local bone formation in critical-sized femoral defects (Figure A,B) . Similarly, heparin covalently conjugated to a hyaluronan hydrogel led to a sustained release of TGF-β1 and significantly enhanced the chondrogenic behavior of encapsulated human chondroprogenitor cells (Figure C,D) .…”
Section: Noncovalent Techniquesmentioning
confidence: 99%